2022
DOI: 10.31235/osf.io/zhvn5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Bordering on Excess”: Perceptions of Fan Obsession in Anime Fans, Furries, and Star Wars Fans

Abstract: In the present research, we examine what it means for fans to take their interests “too far” in a multi-fandom, qualitative study. Specifically, we asked self-identified anime fans, furries, and Star Wars fans to describe what, to them, marked the point where a fan could be said to be taking their interest too far. From these responses we extracted five common themes across fandoms: (1) when one’s fan interest negatively impacts their life, (2) when one’s fan interest becomes the sole or defining feature of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Fans are ardent and enthusiastic supporters of an interest whose passion is sufficiently strong that it becomes a part of their social identity (Reysen & Branscombe, 2010; Reysen et al, 2015). Fans’ interests can vary widely, ranging from interest in a particular piece of media (e.g., a TV show, video game, musician, or film franchise) to a specific hobby or activity (sports, model train collecting, knitting).…”
Section: Fans Stigma and Prejudicementioning
confidence: 99%
See 2 more Smart Citations
“…Fans are ardent and enthusiastic supporters of an interest whose passion is sufficiently strong that it becomes a part of their social identity (Reysen & Branscombe, 2010; Reysen et al, 2015). Fans’ interests can vary widely, ranging from interest in a particular piece of media (e.g., a TV show, video game, musician, or film franchise) to a specific hobby or activity (sports, model train collecting, knitting).…”
Section: Fans Stigma and Prejudicementioning
confidence: 99%
“…Despite the prevalence of prejudice directed toward nonprototypical fan cultures, both in mainstream media and in face-to-face interactions (Plante et al, 2017), there has been relatively little research dedicated to understanding the mechanisms driving this prejudice. As a social identity, there is reason to believe that the social–cognitive processes underlying the treatment of fan cultures should be analogous to the processes at work in other, nonfan groups (Reysen et al, 2015; Tajfel & Turner, 1979). This would certainly seem to be the case when it comes to the link between nonprototypicality and prejudice, which has been observed both in members of racial minorities and in members of nonprototypical fan cultures (Devos & Banaji, 2005; Reysen & Shaw, 2016; Sibley, 2010; Wenzel et al, 2007).…”
Section: Fans Stigma and Prejudicementioning
confidence: 99%
See 1 more Smart Citation
“…These motivations may be similar to what ACG doujin creators are facing. One study indicated that anime fans are susceptible when it comes to discrimination and stereotype, with non-fans referring to them as "socially awkward nerds who are detached from reality", thus putting them at potential risk of isolation [22]. Although there is no direct evidence indicating that ACG doujin creators face the similar situation as autistic people and have the similar motivation to camou age themselves, the possibility is high due to the overlapping feature of two groups.…”
Section: Introductionmentioning
confidence: 99%